Impact of brewery waste on the productive and reproductive indices in Jersey crossbred dairy cattle: Impact of brewery waste on productive and reproductive indices - Balakrishnan, Rajesh Kumar (Indian Journal of Dairy Science, 2024)
The study was conducted in twenty four Jersey crossbred dairy cows for a period of one year with three treatments to study the impact of brewery waste on productive and reproductive indices. The control group (T0) and brewery waste (T1) treatment was carried out in first farmer’s field and balanced ration (T2) treatment was carried out in second farmer’s field with eight animals in each group. The control, brewery and balanced ration animals were fed as per traditional and standard feeding practices. Productive indices viz., Milk yield, Milk fat, Solids Not fat (SNF), Body weight were assessed before and at the end of experiment. Reproductive indices viz., Lactation period, dry period and number of services per conception (SPC) were also assessed. The results of the study indicated that for T1, milk yield and body weight increased significantly (P